Shiloh - Phyllis Reynolds Naylor
What is the right thing to do when a dog is being abused - and belongs to someone else? What about when someone else owns a gun? these are questions Marty finds himself facing but he discovers soon that it is not always easy to separate right from wrong and sometimes all you can do is try to save the ones you love.